Fabrication of Fully Fluorinated Graphene Nanosheets Towards High‐Performance Lithium Storage. Issue 4 (28th March 2014) - Zhan, Liang; Yang, Shubin; Wang, Yun; Wang, Yanli; Ling, Licheng; Feng, Xinliang
<x xml:space="preserve">Abstract</x> Fully fluorinated graphene (F‐graphene) nanosheets are fabricated via a simple liquid exfoliation of fluorinated graphite. The resulting F‐graphene nanosheets have a very high fluorine content (49.7 at%), 2D, amorphous‐like microstructure and thin nature (10 nm). These features render abundant fluorinate active sites for lithium storage and facilitate the rapid diffusion of Li ions during charging and discharging. The resulting F‐graphene nanosheets not only delivery a high reversible capacity of 780 mAh g−1, but also exhibit high‐rate capability and good cycle performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>